Drug Management Quality During the Covid-19 Pandemic at Inpatient Health Centers in Kendari City - Sabarudin Sabarudin; Sunandar Ihsan; Fifi Nirmala; Rifa’atul Mahmudah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2022)
Background: WHO has declared Covid-19 a global pandemic after the infection case reached more than 121,000 cases. Puskesmas is the primary service closest to the community, so it has a significant role in dealing with COVID-19. The quality of health services at Puskesmas was influenced by drug management. On the other hand, the COVID-19 pandemic has resulted in changes in health services at Puskesmas. Hence, it is necessary to evaluate the quality of drug management at Puskesmas during the Covid-19 pandemic. Aims: This study aimed to evaluate the quality of drug management during the COVID-19 pandemic in all inpatient Puskesmas in Kendari City. Methods: This research was descriptive non-experimental, with retrospective data collection in all inpatient Puskesmas in Kendari City during the COVID-19 pandemic. Research subjects were indicators used by Satibi, and research objects include drug stock cards, LPLPO, RKO, and several other documents. The instruments used were observation sheets and interview guides. Results: All puskesmas were still active in proposing drugs to Fornas. The percentage of compliance of available drug items with Fornas, planning accuracy, conformity of requests, and the suitability of receipts was not up to standard. Storage according to dosage form, temperature, LASA, and FEFO were per standards, distribution accuracy, empty stock, insufficient stock, safe stock, the excess stock was not meet standards, and there were expired or damaged drugs. The suitability of the physical amount of the drug met the standard, but there were no inpatient health centers that conducted periodic drug management evaluations during 2020. Conclusion: The quality of drug management during the COVID-19 pandemic in all inpatient Puskesmas in Kendari City had not fully met the standards that have been set.